(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of this study was to find out the influence the professionalism of employees had on the quality of public services at the Office of Population and Civil Registry of Bone Regency. This study used quantitative research with associative research type. The technique used simple random sampling. The target was the Population and Civil Registry Office of Bone Regency with a total sample of 27 people. Data collection techniques used observation, questionnaires and documentation. The data analysis technique used simple linear regression analysis. The validity of the data using validation and reliability tests. The results of this study indicated that the professionalism of employees affects the quality of service at the Office of Population and Civil Registration of Bone Regency. This was proved from the output of the capital summary obtained by R of 0.961 from the large influence of the independent variable or professionalism (X) on the dependent variable or service quality (Y) which was also strengthened by the value of the coefficient of determination (R Square) or the determinant coefficient of 0.921, it meant 92.1% .